2023
DOI: 10.1073/pnas.2301884120
|View full text |Cite
|
Sign up to set email alerts
|

Plant lysin motif extracellular proteins are required for arbuscular mycorrhizal symbiosis

Abstract: Arbuscular mycorrhizal fungi (AMF) can form a mutually beneficial symbiotic relationship with most land plants. They are known to secrete lysin motif (LysM) effectors into host root cells for successful colonization. Intriguingly, plants secrete similar types of LysM proteins; however, their role in plant–microbe interactions is unknown. Here, we show that Medicago truncatula deploys LysM extracellular (LysMe) proteins to facilitate symbiosis with AMF. Promoter analyses demonstrated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 46 publications
0
19
1
Order By: Relevance
“…The RLK gene family represents one of the largest gene families within the plant genome and is also one of the major types of plant receptors responsible for the perception of diverse self and alien signals from abiotic and biotic stresses [19,30,31]. The comprehensive analysis of RLK genes in an increasing number of sequenced plant genomes has not only contributed to a better understanding of the origin, evolution, and functional divergence of this important gene family but has also provided invaluable resources for the identification of functional genes that are valuable for crop breeding [32][33][34][35][36][37]. In this study, the genome-wide identification and evolutionary analysis of RLK genes from D. alata provides additional insights into the evolution and functional roles of the RLK gene family, including its ancient divergence by means of considerable WGDs/SDs, rapid "birth to death" during speciation, and potential roles in disease resistance against anthracnose.…”
Section: Discussionmentioning
confidence: 99%
“…The RLK gene family represents one of the largest gene families within the plant genome and is also one of the major types of plant receptors responsible for the perception of diverse self and alien signals from abiotic and biotic stresses [19,30,31]. The comprehensive analysis of RLK genes in an increasing number of sequenced plant genomes has not only contributed to a better understanding of the origin, evolution, and functional divergence of this important gene family but has also provided invaluable resources for the identification of functional genes that are valuable for crop breeding [32][33][34][35][36][37]. In this study, the genome-wide identification and evolutionary analysis of RLK genes from D. alata provides additional insights into the evolution and functional roles of the RLK gene family, including its ancient divergence by means of considerable WGDs/SDs, rapid "birth to death" during speciation, and potential roles in disease resistance against anthracnose.…”
Section: Discussionmentioning
confidence: 99%
“…Yu et al . (2023) reported that chitin binds to lysM extracellular (LysMe) MtLysMe1/2/3 to impair the immune response. GhWAK7A was used to represent the immune response (Wang et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Zeng et al (2020) found that the LysM domain protein, RiSLM, C. reported that OsMYR1, a receptor-like kinase involved in AM fungal recognition, negatively regulates resistance to the fungal pathogen Magnaporthe oryzae and that the resistance gene OsCEBiP also negatively affects AM symbiosis (C. . Yu et al (2023) reported that chitin binds to lysM extracellular (LysMe) MtLysMe1/2/3 to impair the immune response. GhWAK7A was used to represent the immune response (Wang et al, 2020).…”
Section: Am Symbiosis Improved Immunity But Immunity Suppressed Am Sy...mentioning
confidence: 99%
“… 7 To establish a successful infection in plant roots, AMF can suppress plant immunity through LCO, short-chain CO, or secreted effectors and proteins. 7 , 40 , 46 , 47 , 48 , 49 However, how plants discriminate between the activation of immunity and symbiosis signaling remains unknown.…”
Section: Introductionmentioning
confidence: 99%